Epidemiology and treatment of osteoporosis in women: an Indian perspective - Khadilkar AV; Mandlik RM (Dove Medical Press, 2015)
Anuradha V Khadilkar, Rubina M Mandlik Growth and Endocrine Unit, Hirabai Cowasji Jehangir Medical Research Institute, Jehangir Hospital, Pune, Maharashtra, India Abstract: The number of women with osteoporosis, ie, with reduced bone mass and the disruption of bone architecture, is increasing in India. While data on prevalence of osteoporosis among women in India come from studies conducted in small groups spread across the country, estimates suggest that of the 230 million Indians expected to be over the age of 50 years in 2015, 20%, ie, ~46 million, are women with osteoporosis. Thus, osteoporosis is a major public health problem in Indian women. Low calcium intakes with extensive prevalence of vitamin D deficiency, increasing longevity, sex inequality, early menopause, genetic predisposition, lack of diagnostic facilities, and poor knowledge of bone health have contributed toward the high prevalence of osteoporosis. Bone health may be optimized by creating an environment to achieve peak bone mass during adolescence, maintenance of healthy bone throughout the life cycle, and prevention of bone loss postmenopausal. In Indian women, calcium, vitamin D, and bisphosphonates are the commonest first-line therapies used. The use of other drugs such as hormone replacement therapy, estrogen agonists, calcitonin, parathyroid hormone, and denosumab is decided as per the affordability and availability of treatment options. Major gaps still remain in the diagnosis and management of osteoporosis, thus highlighting the need for more structured research in this area. This review focuses on the epidemiology of osteoporosis in Indian women and available treatments. Keywords: osteoporosis, Indian perspective, epidemiology, treatment